A reversed‐phase ultra‐fast liquid chromatography–photodiode array detector (RP‐UFLC‐PDA) method for simultaneous estimation of ayapanin and umbelliferone in Ayapana triplinervis Vahl. (8th February 2022) - Biswas, Sayan; Kar, Amit; Chanda, Joydeb; Sharma, Nanaocha; Bharadwaj, Pardeep Kumar; Haldar, Pallab Kanti; Mukherjee, Pulok Kumar
Abstract: A rapid validated ultra‐fast liquid chromatography–photodiode array detector (UFLC‐PDA) method was developed to identify and quantify ayapanin (AY) and umbelliferone (UM) simultaneously in Ayapana triplinervis Vahl methanolic extract. The method was validated for linearity, limit of detection (LOD; 3:1σ/S), limit of quantification (LOQ; 10:1σ/S), precision, accuracy, specificity and robustness. The response was linear with a good correlation between concentration and mean peak area through a correlation coefficient of 0.9996, y = 7025.7x – 2269.8 and 0.9997, y = y = 16, 262x – 946 with LOD of 6.256 ± 0.52 and 3.325 ± 0.36, and LOQ of 18.838 ± 0.18 and 8.870 ± 0.85 for AY (0.67% w/w) and UM (0.18% w/w), respectively. The relative standard deviation (%) of precision and recovery of AY and UM was <2.0%. The proposed method was simple, accurate, specific, precise and reproducible.